Westonci.ca is the best place to get answers to your questions, provided by a community of experienced and knowledgeable experts. Our Q&A platform provides quick and trustworthy answers to your questions from experienced professionals in different areas of expertise. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.

if the first term is -2 and the rule is multiply by 6 and then subtract 13 whats the 3rd term

Sagot :

Answer:

-163

Step-by-step explanation:

-2,-25,-163

-2×6=-12 -12-13=-25

-25×6=-150 -150-13=-163

Answer:

The third term is = -163

Step-by-step explanation:

The first term is = -2

The second term = -2 ×6 = -12 Then - 13 = - 25

The second term = - 25

The third term = -25 × 6 = - 150 Then -13 = -163

The third term is -163

Mark brainliest